Organotrisulfide: A High Capacity Cathode Material for Rechargeable Lithium Batteries. (13th July 2016) - Wu, Min; Cui, Yi; Bhargav, Amruth; Losovyj, Yaroslav; Siegel, Amanda; Agarwal, Mangilal; Ma, Ying; Fu, Yongzhu
Abstract: An organotrisulfide (RSSSR, R is an organic group) has three sulfur atoms which could be involved in multi‐electron reduction reactions; therefore it is a promising electrode material for batteries. Herein, we use dimethyl trisulfide (DMTS) as a model compound to study its redox reactions in rechargeable lithium batteries. With the aid of XRD, XPS, and GC‐MS analysis, we confirm DMTS could undergo almost a 4 e − reduction process in a complete discharge to 1.0 V. The discharge products are primarily LiSCH3 and Li2 S. The lithium cell with DMTS catholyte delivers an initial specific capacity of 720 mAh g −1 DMTS and retains 82 % of the capacity over 50 cycles at C/10 rate. When the electrolyte/DMTS ratio is 3:1 mL g −1, the reversible specific energy for the cell including electrolyte can be 229 Wh kg −1 . This study shows organotrisulfide is a promising high‐capacity cathode material for high‐energy rechargeable lithium batteries.